The Geological Signature of Great Earthquakes off Canada's West Coast - Clague, John; Bobrowsky, Peter (Geoscience Canada, 1999)
Summary Geological and geophysical evidence, gathered in the last 15 years by a number of scientists working in Canada and the United States, leaves little doubt that some of the largest earthquakes on Earth occur at the Cascadia subduction zone on Canada's western doorstep. No such earthquake has occurred since European settlement of the region in theearly 1800s, but the entire 900 km length of the thrust fault separating the Juan de Fuca and North America plates apparently ruptured during a magnitudes event on 26 January 1700. Evidence for this and older subduction earthquakes has been found at coastal wetlands from Vancouver Island to northern California. The geological evidence includes buried wetland soils produced by sudden, seismically induced subsidence, sheets of sand and gravel deposited by tsunamis, and sand dyke sand blows generated by lique faction during strong ground shaking. Dating of the buried soils and tsunami deposits in Washington and Oregon hassh own that great Cascadia earthquake shave an average recurrence of 500 years; however, intervals between the seven most recent events range fromless than 200 years to 700-1300 years.The hypothesis that subduction earthquakes occur in Cascadia is independently supported by geodetic measurements and the results of geophysical modelling, which collectively indicate that part of the plate boundary is locked and accumulating elastic strain that will be released during a future earthquake.